2018
DOI: 10.1080/10962247.2017.1409294
|View full text |Cite
|
Sign up to set email alerts
|

Protection from wintertime rainfall reduces nutrient losses and greenhouse gas emissions during the decomposition of poultry and horse manure-based amendments

Abstract: The impact of rainfall protection on nutrient losses and GHG emissions was monitored during the decomposition of broiler chicken, turkey, and horse manure-based soil amendments. Amendments exposed to rainfall had large ammonium and potassium losses, resulting in a 37-74% decrease in N inputs when compared with amendments protected from rainfall. Nitrous oxide emissions were also higher with rainfall exposure, although it had no effect on carbon dioxide and methane emissions. Overall, this work highlights the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Carbon dioxide emissions appeared to be higher in poultry relative to horse MBSAs, which is consistent with temporal changes in C concentration measured with FTIR, and the greater CO 2 emissions and mineralization rates previously reported for poultry MBSAs (Castellanos and Pratt, 1981;Gagnon and Simard, 1999). In contrast, the seemingly higher CH 4 emissions observed in horse as opposed to poultry MBSAs are similar to field observations made by Maltais-Landry et al (2018) and provide valuable information on GHG emissions from understudied horse and turkey MBSAs. Finally, a lower contribution of CH 4 emissions to C losses than CO 2 in solid manures is consistent with Hao et al (2004).…”
Section: Carbon Cyclingsupporting
confidence: 88%
See 3 more Smart Citations
“…Carbon dioxide emissions appeared to be higher in poultry relative to horse MBSAs, which is consistent with temporal changes in C concentration measured with FTIR, and the greater CO 2 emissions and mineralization rates previously reported for poultry MBSAs (Castellanos and Pratt, 1981;Gagnon and Simard, 1999). In contrast, the seemingly higher CH 4 emissions observed in horse as opposed to poultry MBSAs are similar to field observations made by Maltais-Landry et al (2018) and provide valuable information on GHG emissions from understudied horse and turkey MBSAs. Finally, a lower contribution of CH 4 emissions to C losses than CO 2 in solid manures is consistent with Hao et al (2004).…”
Section: Carbon Cyclingsupporting
confidence: 88%
“…The effects of the M20 treatment were substantial for horse MBSA, where high CO 2 emissions and C losses combined with low N losses increased total N and lowered C/N. These apparent benefits of decomposition in understudied horse MBSA are similar to field observations made by Maltais-Landry et al (2018). However, high O 2 availability in the M20 treatments resulted in high CCE, especially in poultry MBSAs, similar to what Chowdhury et al (2014) observed, highlighting potential tradeoffs between maintaining the nutrient value of MBSAs during decomposition and minimizing CCE.…”
Section: Mbsasupporting
confidence: 69%
See 2 more Smart Citations
“…However, when comparing the food waste composts, less TN was recovered as PAN in the industrial compost than the non-industrial food waste compost (Table 3), which could be due to the addition of wood residues in the Ecoscraps product, similar to yard waste municipal composts that release little PAN [14,16]. Alternatively, this may be due to N losses occurring during longer composting and/or storage periods for industrial products, especially if piles were not protected from rainfall [34]. Furthermore, the industrial cow manure-based compost (Black Kow) likely immobilized N in the Lake soil whereas it had little effect on the other soil, consistent with the lower impact on soil N of industrial as opposed to non-industrial manure products reported by Gagnon and Simard [31].…”
Section: The Effects Of Feedstock and Composting Processmentioning
confidence: 99%